Computational analysis of adhesion between a cancer cell and a white blood cell in a bifurcated microvessel. (April 2020) - Khorram, Asghar; Vahidi, Bahman; Ahmadian, Bahram
Highlights: The effect of vessel branching on the probability of adhesion between a cancer cell and a white blood cell was evaluated. The adhesion of the cancer cell with the white blood cell was investigated computationally using FEM and FSI methods. The velocity, von misses stress, and separation distance of the cancer cells in the bifurcation vessel were compared with the same problem in a straight vessel. The effect of vessel branching on the probability of adhesion and velocity of the cancer cell was remarkable and it is worthy to be considered in the cancer cell metastasis investigations. Abstract: Background and Objective: Cancer is one of the diseases caused by irregular and uncontrolled growth of cells and their propagation into various parts of the body. The motion and adhesion of cancer cells in a blood vessel is a critical step in tumor progression that depends on some vascular parameters such as vessel branching. In this study, effect of microvessel branching on the bonds between a cancer cell and a white blood has been investigated as compared to an analogous problem in a straight vessel. Methods: The analysis is performed using finite elements and fluid-structure interaction methods. Moreover, the equations for adhesion of the cancer cell to white blood cell are coded in MATLAB for calculating forces between them and the code is coupled directly and simultaneously with the COMSOL software. For fluid-structure interaction analysis, it is assumed that the properties of the blood and the cells are homogeneous and the fluid is incompressible and Newtonian. Cancer cell is modeled as a rigid body and white blood cell is assumed as linear elastic. Results: The results show that although the geometry of the vessel does not affect on the separation distance of cancer cell considerably, but at the area near a bifurcation, high fluctuations in cancer cell velocity is occurred due to increasing in number of bond formation between the cancer cell and the white blood cell. Accordingly, it can be predicted that higher concentration of adhered particles occurs near the bifurcations. Moreover, shear stress at the point of contact of the cancer cell and the white blood cell in the branched vessel is greater than that in the straight path. In addition to, the probability of breaking of the bond between the cancer cell and the white blood cell increases in the branched vessel. Conclusions: Through consideration in the adhesion charts of this study along with observations from medical interventions such as drug delivery to cancer patients, considerable developments on the treatment or prevention of cancer metastasis may be achieved.